PENGARUH PELATIHAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN STUDI PADA KARYAWAN PERUSAHAAN HUTAN TANAMAN INDUSTRI ( HTI ) - -, Try Wahyudi (EKONOMIA, 2018)
This study aims to determine whether Job Training and work environment have an effect on to Employee Performance of Industrial Plantation Company (HTI). Independent variable in this research is job training and work environment while dependent variable is employee performance. This research was conducted on employees of Industrial Timber Plantation Company (HTI) consisting of 95 respondents. According to Rivai and Sagala (2011: 212): training is the process of systematically changing employee behavior to achieve organizational goals. Training is related to the skills and abilities of employees to carry out current work. The type of research used is quantitative research. Methods of data collection using questionnaires. Data analysis used multiple linear regression. The results showed that job training and work environment have a significant positiveeffectonemployeeperformance.Â Â The conclusions of this study suggest that the three proposed hypotheses are proved or the three hypotheses accepted. This means that job training and work environments have significant posi- tive impact on employee performance in improving company productivity.